HTML Texts and the Dawn of Asemic Digital Literature: Exploring Dennis Cooper’s Ideas - Barrows, Cameron (Text Matters: A Journal of Literature, Theory and Culture, 2023)
Dennis Cooper’s HTML texts which use Graphic Interchange Format (GIFs) instead of traditional glyph-based text, exhibit the extremities of our times, both thematically and structurally, through the radical temporality of the GIFs. The digital geometry of these texts is constructed through the juxtaposition of GIFs. This has allowed Cooper to construct and explore a new pictorial language predicated upon metamorphosis, flow, and flux. Cooper’s HTML texts highlight the motifs of human fallibility, contingency, and finitude, culminating in a rejection of the rationalist and idealist conceptions of what a novel is. Focusing on the structural and hermeneutical aspects of the HTML texts, rather than the ephemeral content of the GIFs themselves, allows for the proposition of a new digital hermeneutics and skepticism necessary for literary exegesis in our increasing digital world. Through an examination of the theoretical implications of Cooper’s HTML texts, one can trace the future frontiers of digital literature and its necessary hermeneutics.